Calcium complex of 2, 5-dihydroxybenzoic acid (gentisic acid): synthesis, crystal structure, and spectroscopic properties. Issue 16 (17th August 2016) - Kalinowska, M.; Mazur, L.; Regulska, E.; Korczak, A.; Świderski, G.; Lewandowski, W.
Abstract: The synthesis, crystal structure, and spectral characteristics (IR, Raman, and 1 H and 13 C NMR) of a monomeric hexa(aqua)calcium compound, viz. [Ca(C7 H5 O4 )2 (H2 O)6 ]·H2 O (C7 H5 O4 = 2, 5-dihydroxybenzoate), are reported. The central Ca(II) located on a twofold axis is eight coordinate in an approximate square antiprismatic environment, bonded to two monodentate 2, 5-dihydroxybenzoate ligands via the carboxylate oxygen, and six waters. The adjacent monomeric units are linked with the aid of several O–H⋯O hydrogen bonds. Abstract :